Los efectos de la reinserción a la sociedad y las medidas socioeducativas en los adolescentes infractores - Pingos Tarco, Victor Daniel (2025)
The study analyzes the effectiveness of the socio-educational measures implemented in Ecuador, highlighting the challenges that arise in the social reintegration of adolescent offenders, contrasting legal theory with practical reality. The research addresses the central problem of the disproportionate flexibility of these measures, the complex socioeconomic factors, the lack of opportunities and inadequate conditions in detention centers that hinder social reintegration and the lack of adequate follow-up, which contributes to criminal recidivism. The implementation of a mixed methodological approach, through the use of qualitative and quantitative techniques such as interviews and surveys, allows for an in-depth exploration of the Ecuadorian juvenile justice system and the reality of juvenile detention. Explanatory research is applied, which seeks to determine and explain the effect of socio educational measures and the phenomena that impacts the social reintegration of adolescent offenders. The interviews reveal social obstacles such as discrimination, lack of job opportunities, absence of comprehensive public policies and lack of monitoring. This research highlights that complex socioeconomic factors contribute to the ineffectiveness of social reintegration, exposing adolescents to an environment of lack of opportunities and adversity.